An in situ study on the effect of grain boundaries on helium bubble formation in dual beam irradiated FeCrAl alloy. (15th February 2023) - Sun, Tianyi; Niu, Tongjun; Shang, Zhongxia; Chen, Wei-Ying; Li, Meimei; Wang, Haiyan; Zhang, Xinghang
Abstract: FeCrAl alloy is one of the promising cladding materials in the advanced nuclear reactors. Here we compare the irradiation response of the nanolaminate (NL) and coarse-grained (CG) FeCrAl alloys, by performing He ion irradiation followed by in situ Kr ion irradiation in a transmission electron microscope at 450 °C. NL alloy has reduced He bubble induced swelling and decreased the density of dislocation loops in comparison to the CG alloy. The distribution of He bubbles appears to be dependent on misorientation angles of high angle grain boundaries. A new type of nanoprecipitates was identified in the irradiated CG FeCrAl without noticeable chemical segregation. Chemical segregation occurred along the laminate boundaries in the irradiated NL FeCrAl alloy. Graphical abstract: Image, graphical abstract